CONCEPT OF DETERMINING PRICES FOR ORGANIC VEGETABLES IN IMPROVING FARMERS WELFARE - Nurohmah, Lisda; Sugiartiningsih; Noor, Qur'ani; Suarsa, Abin; Bagianto, Agus (PT. Antis International Publisher, 2024)
The aim of the research is to determine the mechanism and implications of pricing organic vegetables implemented by PT Bionic Farm on the welfare of CV Karunia Abadi Farm farmers. The research method uses a quantitative approach in the form of vegetable sales reports and a qualitative approach to analyze farmer welfare. The calculation results show that the mechanism for setting prices for organic vegetables is determined by the distributor, namely PT Bionic Farm, so that the role of farmers is only limited to price takers. The impact in terms of farmers' income is seen to receive quite a large margin as evidenced by the wages for organic vegetable care services received by farmers above the Regional Minimum Wage (UMR). Meanwhile, farmers have to bear large expenditures for capital and labor in producing organic vegetables such as asparagus. The solution is that farmers must be given socialization on determining the Cost of Goods Sold (HPP) for organic vegetables through Community Service (PkM) activities in order to encourage farmers to increase their productivity in real terms, thereby improving Indonesia's economic welfare.